2021
DOI: 10.21272/mmi.2021.2-08
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and priorities in talent management during the global pandemic caused by COVID-19

Abstract: The paper deals with the talent management issue as one of the effective human resource management practices during the global pandemic caused by COVID-19 and points to the main challenges and priorities in the research area. Talent management has undergone a dynamic development in recent years. It has recently become a frequently discussed concept among business and academics alike and one of the priorities of the modern management of all companies. The paper also presents the results of research carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 14 publications
(9 reference statements)
2
22
0
1
Order By: Relevance
“…The themes highlighted in the semi-structured interviews in this study corroborate articles found in the existing literature. Most of the past studies identified a competitive job market (King & Vaiman, 2019;Tomcikova et al, 2021), recruiter's workload and time-consuming when a greater number of candidates appeared for the job (Cohen, 2019;Mishra et al, 2021), restrictive government policy that challenges employee hiring process (Phelan, 2020), insufficient recruitment turnaround time (Tumasjan et al, 2020), and recruitment difficulties during the Covid-19 pandemic (Joshi et al, 2020;Kalogiannidis, 2021) as the recruiters' challenges and they are aligned with the finding of this study. Yet, academics disregard the school's location since most previous studies have focused on the public school environment, where teachers have little say in site choices.…”
Section: Discussionsupporting
confidence: 78%
“…The themes highlighted in the semi-structured interviews in this study corroborate articles found in the existing literature. Most of the past studies identified a competitive job market (King & Vaiman, 2019;Tomcikova et al, 2021), recruiter's workload and time-consuming when a greater number of candidates appeared for the job (Cohen, 2019;Mishra et al, 2021), restrictive government policy that challenges employee hiring process (Phelan, 2020), insufficient recruitment turnaround time (Tumasjan et al, 2020), and recruitment difficulties during the Covid-19 pandemic (Joshi et al, 2020;Kalogiannidis, 2021) as the recruiters' challenges and they are aligned with the finding of this study. Yet, academics disregard the school's location since most previous studies have focused on the public school environment, where teachers have little say in site choices.…”
Section: Discussionsupporting
confidence: 78%
“…Special attention should be paid to studies in which the problems of medical institutions occupy a special place and significantly reduce the efficiency of the entire medical system nationwide. In particular, studied the labor market of medical workers and proved that it was significantly affected by the impact of the pandemic [ 13 ]; based on the experience of the USA, considered the differences in actual medical protocols [ 14 ]; studied labor resource management mechanisms in hospitals and other medical institutions [ 15 ]; also based their research on labor resources and their transformation during the pandemic [ 16 ]; and examined the quality of public service in terms of the provision of medical services, which catalyzed improving the efficiency of the medical system during the pandemic [ 17 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Special attention should be paid to the accelerated development of ICT and digital innovations, the promotion of non-cash payments in the context of the Covid-19 pandemic in studies of Civelek et al (2021), Sawangchai et al (2020), Bilan et al (2020b), etc. Many research deal with the impact of the Covid-19 pandemic on the daily public lives (Tomcikova et al 2021;Chmielecki, 2021;Kolosok & Jakubowska 2020), economic indicators of countries' growth (Tiutiunyk et al, 2021a;Mishenina et al 2021;Przytuła et al 2020;Liu et al 2021;Dementiev, 2021;Polinkevych et al 2021), social issues (Kadar & Reicher, 2020;Stefan et al 2020) and financial issues of development (Hinrichs & Bundtzen, 2021;Pardal et al 2020). So, the studies on the relationship between the pandemic effects and (2020) hypothesized that there is a relationship between pandemic lockdown and social, economic and environmental development indicators.…”
Section: Literature Reviewmentioning
confidence: 99%